Manajemen Program Ekstrakulikuler Bahasa Arab di Madrasah - Kamilaini, Azka; Agustina, Rahmah Fadhilah; Haqiqy, M. Syihabul Ihsan Al; Mufidah, Nuril (Qismul Arab: Journal of Arabic Education, 2024)
This research aims to describe the management of extracurricular programs in madrasas, how the planning of extracurricular programs is carried out, and the organization, implementation, and evaluation of Arabic language programs in madrasah.  This research uses a qualitative approach of case study type.  The research subject was Madrasah Aliyah AL-Rosyid Bojonegoro, Indonesia, in 2024. Data collection techniques used were observation, interviews, and documentation. Data analysis used Milles and Huberman's model through three stages: condensation, presentation, and conclusion drawing. The results of this study indicate that the management is made through stages, namely needs analysis and compiling a work program (PROKER), which is prepared every semester in the form of extracurricular time allocations, activity schedules and materials. Organizing in the form of creating an organizational structure along with their respective roles to support running the madrasah/school extracurricular program. Program implementation involves activities such as intensive training for extracurricular coaches, class visits to observe and provide direct feedback, and effective communication patterns between students and teachers. Extracurricular programs at MA Al Rosyid are divided into diniyah as a continuous extracurricular program and periodic extracurricular programs such as muhadharah training and Arabic MC training. Several evaluations are conducted, and daily evaluations focus on achieving daily learning objectives and providing immediate feedback. Weekly evaluation involves assessing student progress in language skills and adapting teaching methods as needed. Monthly evaluations include a thorough reflection on the effectiveness of the program and an improvement plan. Annual evaluations aim to assess the program's overall impact on students' Arabic language proficiency and the achievement of long-term goals.